Role of Managerial Accounting Information System in Improving the Value Chain and its Impaction Evaluation Performance: دراسة حالة في الشركة العامة لصناعة الزيوت النباتية (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The performance measures and traditional methods used in management accounting is no longer able to provide convenient to evaluate the performance of economic units in the modern manufacturing environment information، and so this information is more important and feasibility must be Mistohat of all the company's activities and functions، and it is a problem Find the inadequacy of information management accounting that contribute to meet the needs of the upper levels of management to cope with the problems resulting from the increased size and complexity of the business، and lack of management accounting information and methods used in the performance evaluation، which reflected negatively on the value chain activities and then on the performance in the process of evaluating the economic unit. So this research seeks to review aspects of the role of management accountinginformation to serve senior management and keep up with the circumstances and variables in the current business environment، and explain how the role of management accounting information system to evaluate the performance and improve the value chain activities in accordance with the modern methods of the General Company for Vegetable Oil Industry system، and is based on research into basic assumptions that the system of management accounting role in meeting the information needs of different administrative levels to face the problems resulting from the breadth and complexity of the business competition and the multiplicity of its size، and the system of management accounting role in improving the information and evaluate the activities of the value chain.